TRANSFORMASI KEPRIBADIAN DAN KEDISIPLINAN MAHASISWA MELALUI PAGUYUBAN DUTA KAMPUS - Urmilawati, Suci; Qosim Mubah, Hilmi (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2025)
The IAIN Madura Campus Ambassador Association is a forum for students to develop their personality and discipline. This study aims to analyze how this association contributes to transforming students' character and disciplinary attitudes. This research uses a descriptive qualitative approach, data is collected through in-depth interviews, observations, and documentation. The analysis is available using the Miles and Huberman model with stages of data condensation, data display, and conclusion drawn. Data validity applies triangulation of sources and methods. The results of the study show that the IAIN Madura Campus Ambassador Association plays an important role in shaping the personality and discipline of students. Through various trainings and activities, students experience an increase in responsibility, academic discipline, leadership, and social skills. Active involvement in this association also forms an adaptive, professional, and open-minded character. Thus, the association plays a strategic role in producing students who are not only academically superior, but also ready to face the challenges of the world of work and social life.